2010
DOI: 10.1111/j.1467-9450.2009.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and PTSD in a Faroese youth total-population sample

Abstract: The prevalence of twenty traumatic events and negative life events in relation to posttraumatic stress disorder (PTSD) was studied in a Faroese total-population sample of 687 eighth-grade students with a mean age of 14.2 years. Ninety-four percent of the females and 89% of the males were directly exposed to or had witnessed at least one traumatic event or a negative life event. The odds ratios for PTSD after direct and indirect exposure to specific events are described. The lifetime prevalence of PTSD was 20%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 24 publications
8
34
0
Order By: Relevance
“…Findings suggest that living in a single-parent household is strongly correlated with development of PTSD (11,12,14,15). This may be attributable to a lack of stable role-models, parental supervision, or to conflicts between separated parents (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings suggest that living in a single-parent household is strongly correlated with development of PTSD (11,12,14,15). This may be attributable to a lack of stable role-models, parental supervision, or to conflicts between separated parents (21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the comparison studies in Iceland, Lithuania, Denmark and The Faroe Islands, it was suggested that girls may be more exposed to in-family related events and self-inflicted events, whereas boys more often appear to be victimised in activities outside of the family (15). However, later comparison studies from India and Kenya did not show this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining trauma rates and subsequent negative outcomes among nationally representative populations are common, but until recently, few have focused on adolescent populations [1][2][3]. Evidence shows that by the time an individual reaches adolescence, they are at risk of experiencing at least one traumatic event [4,5], and when compared to adulthood, trauma exposure is at its peak during this time.…”
Section: Introductionmentioning
confidence: 99%
“…This study utilises the full NCS-A student sample (N = 10,123), applying LCA to identify clusters of adolescents sharing similar trauma patterns. Secondly, a larger sample size is submitted to LCA than in previous studies utilising the same analysis tool [1,6], with participants encompassing a wider adolescent age range [1,3]. Thirdly, this study not only looks at individual mental health diagnoses but also examines comorbidity across disorders by looking at the three DSM-IV categories under which they fall (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In three Nordic societies, the prevalence of direct or indirect exposure to traumatic events among 14-and 15-year-old children has been reported to range from 70% to 90% (20)(21)(22)(23); such exposure includes events such as the death of a family member and a serious accident. Despite this high prevalence rate, the majority of the re-victimization literature appears to focus on the relationship between child maltreatment and sexual re-victimization.…”
Section: Introductionmentioning
confidence: 99%